Privatization and structural adjustment in the Arab countries : papers presented at a seminar held in Abu Dhabi, United Arab Emirates, December 5-7, 1988 - El-Naggar, Saʻid, 1920- (International Monetary Fund, 1989)
This seminar volume, edited by Said El-Naggar, examines the challenge that Arab countries with large public sectors face in placing the privatization process within the wider context of structural change.
Keywords: Privatization -- Arab countries -- Congresses.; Arab countries -- Economic policy -- Congresses.; Structural adjustment (Economic policy) -- Arab countries -- Congresses.; Privatisation -- États arabes -- Congrès.; États arabes -- Politique économique -- Congrès.; Ajustement structurel (Économie) -- États arabes -- Congrès.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; Economic policy; Privatization; Structural adjustment (Economic policy); Arab countries; Privatisation -- Pays arabes -- Congrès.; Pays arabes -- Politique économique. -- Congrès.; Conference papers and proceedings